The Management of Human Resources Between Ethics and Practice - Zied Akrout; Mohamed Amine BOURAOUI; Salim Bourchid Abdelkader (International Journal on Humanities and Social Sciences, 2022)
In this paper, we propose an ethical compass to guide the work of HR management in particular tasks where the damage is done to another human being in order to achieve the greatest result. This compass shows the need for organizations to develop responses that protect the well-being of the organization, the victims, and the managers in order to respond to the ethical questions that HRM raises.